Dificuldades sociodiscursivas na escrita académica em estudantes universitários de graduação e pós-graduação - Peralta, Marco Rossi (2023)
Academic-scientific writing represents a challenge for the development of the trajectories of both undergraduate and graduate students. This paper aims at analyzing difficulties in academic writing in a group of undergraduate and postgraduate students from different disciplines who attended a four-month virtual workshop focused on the issue between 2021 and 2022. An analysis of academic texts and metadiscursive testimonies of the participants registered during the pedagogical interaction is carried out, which are complemented by semi-structured interviews. The results show that difficulties in academic writing are associated with different dimensions of the process: knowledge of the characteristics of academic and scientific discursive genres (rhetorical structure and socio-communicative objectives); the immersion of university students in the socialization processes of each genre; representations about writing within a given disciplinary area; training in the writing of argumentative texts in general (for example, difficulty in identifying and maintaining the argumentative thread) and academic texts in particular (citation standards). It is concluded that the scenario described above requires both pedagogical interventions and institutional or community initiatives.